Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Nguyễn Hoàng Tuấn Tú
Xem chi tiết
anh trịnh
4 tháng 12 2021 lúc 20:00

a, \(\dfrac{7}{15}\)+\(\dfrac{18}{54}\)
=  \(\dfrac{7}{15}\)\(\dfrac{1}{3}\)
=  \(\dfrac{7}{15}\)+\(\dfrac{5}{15}\)
=    \(\dfrac{12}{15}\) = \(\dfrac{4}{5}\) =0,8
b, \(\dfrac{12}{25}\)+\(\dfrac{23}{75}\)-\(\dfrac{1}{4}\)
=     \(\dfrac{59}{75}\)   -\(\dfrac{1}{4}\)
=         \(\dfrac{161}{300}\)
   

Nguyễn Hoàng Tuấn Tú
Xem chi tiết
qlamm
4 tháng 12 2021 lúc 19:25

a, 7/15 + 18/54 = 4/5

Quoc Tran Anh Le
Xem chi tiết
Hà Quang Minh
2 tháng 10 2023 lúc 22:53

1) a) (-12).12 = -(12.12) = -144      

    b) 137.(-15) = -(137.15) = - 2 055

2) 5.(-12) = -(5.12) = -60

Nguyễn Công Tú
Xem chi tiết
Nguyễn Ngọc Linh Hương
Xem chi tiết
Nguyễn Thị Thu Phương
Xem chi tiết
Nguyễn Lê Phước Thịnh
27 tháng 7 2021 lúc 22:33

a) \(\sqrt{24+8\sqrt{5}}+\sqrt{9-4\sqrt{5}}\)

\(=2\sqrt{5}+2+\sqrt{5}-2\)

\(=3\sqrt{5}\)

b) \(\sqrt{17-12\sqrt{2}}+\sqrt{9+4\sqrt{2}}\)

\(=3-2\sqrt{2}+2\sqrt{2}-1\)

=2

c) \(\sqrt{6-4\sqrt{2}}+\sqrt{22-12\sqrt{2}}\)

\(=2-\sqrt{2}+3\sqrt{2}-2\)

\(=2\sqrt{2}\)

Kha ly Duong
Xem chi tiết
Minh Hiếu
17 tháng 10 2023 lúc 21:28

a) \(x\left(x^2+4x+5\right)-x^2\left(x+4\right)\)

\(=x^3+4x^2+5x-x^3-4x^2\)

\(=5x\)

b) \(\left(x-2\right)^2+\left(3-x\right)\left(x-1\right)\)

\(=x^2-4x+4+3x-3-x^2+x\)

\(=1\)

c) \(\left(x+2\right)^3-x\left(x^2+6x+12\right)\)

\(=x^3+6x^2+12x+8-x^3-6x^2-12x\)

\(=8\)

 

Trần Quỳnh Như
Xem chi tiết
minh nguyet
4 tháng 4 2021 lúc 22:14

1,

a, \(\left(\dfrac{-4}{3}+\dfrac{1}{3}\right).\dfrac{5}{12}\)=-\(\dfrac{5}{12}\)

b, \(\dfrac{16}{5}+\left(\dfrac{-45}{14}\right):\dfrac{3}{28}\)

=\(\dfrac{-2}{15}\)

2,

a, 2x+19=25

=>x=3

b, \(-\dfrac{2}{9}x=\dfrac{1}{3}\)

=>x=\(\dfrac{-3}{2}\)

Nguyễn Lê Phước Thịnh
4 tháng 4 2021 lúc 22:11

Bài 1: 

a) Ta có: \(\dfrac{-4}{3}\cdot\dfrac{5}{12}+\dfrac{1}{3}\cdot\dfrac{5}{12}\)

\(=\dfrac{5}{12}\cdot\left(\dfrac{-4}{3}+\dfrac{1}{3}\right)\)

\(=\dfrac{-5}{12}\)

b) Ta có: \(3\dfrac{1}{5}+\left(\dfrac{2}{7}-\dfrac{7}{2}\right):\dfrac{3}{28}\)

\(=\dfrac{16}{5}+\left(\dfrac{4}{14}-\dfrac{49}{14}\right):\dfrac{3}{28}\)

\(=\dfrac{16}{5}+\dfrac{-45}{14}\cdot\dfrac{28}{3}\)

\(=\dfrac{16}{5}-30=\dfrac{-134}{5}\)

Rimuru tempest
4 tháng 4 2021 lúc 22:43

1)

a) \(-\dfrac{4}{3}.\dfrac{5}{12}+\dfrac{1}{3}.\dfrac{5}{12}=\dfrac{5}{12}.\left(\dfrac{-4}{3}+\dfrac{1}{3}\right)=\dfrac{5}{12}.\left(-1\right)=-\dfrac{5}{12}\)

b) \(3\dfrac{1}{5}+\left(\dfrac{2}{7}-\dfrac{7}{2}\right).\dfrac{28}{3}=3+\dfrac{1}{5}-\dfrac{45}{14}.\dfrac{28}{3}\)

\(=3+\dfrac{1}{5}-30=-27+\dfrac{1}{5}=-\dfrac{134}{5}\)

2)

a) \(2x+19=25\)

\(2x=25-19=6\)

\(x=3\)

b) \(-\dfrac{2}{9}x-\dfrac{1}{7}=\dfrac{4}{21}\)

\(-\dfrac{2x}{9}=\dfrac{4}{21}+\dfrac{1}{7}=\dfrac{1}{3}\)

\(x=\dfrac{1}{3}.\left(-\dfrac{9}{2}\right)=-\dfrac{3}{2}\)

 

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
3 tháng 4 2019 lúc 14:55

a) Ta được: ( x + 2 ) 2 6 ( x + 2 ) = x + 2 6 ;

b) Ta được: 5 a + 9 5 a 2 b .